2007
DOI: 10.1136/jcp.2006.041756
|View full text |Cite
|
Sign up to set email alerts
|

Copper:caeruloplasmin ratio

Abstract: Investigation of copper status can be a diagnostic challenge. The non-caeruloplasmin-bound copper (NCC) has deficiencies; accordingly, the copper:caeruloplasmin ratio has been suggested as an alternative index of copper status. A reference interval for this index was derived. In addition to making the interpretation of copper easier, the copper:caeruloplasmin ratio should also enable adjustment for relatively high caeruloplasmin concentrations without recourse to producing gender- and age-derived intervals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 10 publications
1
21
1
Order By: Relevance
“…The present study's copper:caeruloplasmin ratio (mean 8 SD, mol/g) of 6.99 8 0.84 ( table 3 ) is similar to 6.81 8 0.87 reported by Twomey et al [9] . Also, the Omani reference range of 5.46-8.14 mol/g for copper:caeruloplasmin ratio ( table 3 ) is close to 5.2-7.3 and 5.08-8.55 mol/g Beetham [8] and Twomey et al [9] reported, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The present study's copper:caeruloplasmin ratio (mean 8 SD, mol/g) of 6.99 8 0.84 ( table 3 ) is similar to 6.81 8 0.87 reported by Twomey et al [9] . Also, the Omani reference range of 5.46-8.14 mol/g for copper:caeruloplasmin ratio ( table 3 ) is close to 5.2-7.3 and 5.08-8.55 mol/g Beetham [8] and Twomey et al [9] reported, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Also, the Omani reference range of 5.46-8.14 mol/g for copper:caeruloplasmin ratio ( table 3 ) is close to 5.2-7.3 and 5.08-8.55 mol/g Beetham [8] and Twomey et al [9] reported, respectively. Furthermore, Omani reference ranges of 10.2-21.3 M (copper) and 0.215-0.427 g/l (caeruloplasmin) are similar to the 10-25 M (copper) and 0.200-0.500 g/l (caeruloplasmin) reported by Twomey et al [9] . However, the observation that the copper:caeruloplasmin ratio was markedly higher in women compared to men ( table 3 ) contrasted with the previous reports [8,9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnostic scoring system has been developed that includes 7 parameters (neurological symptoms, KF rings, Coombs-negative hemolytic anemia, serum ceruloplasmin concentration, urinary copper excretion, liver copper measurement, and genetic mutations) (10 ). Other biochemical markers have been proposed such as serum free copper concentration (11 ) and copper:ceruloplasmin ratio (12 ), but these appear to be less reliable. False-positive and -negative rates are high among the traditional markers.…”
mentioning
confidence: 99%
“…Normalization of NCC in blood reflects the effectiveness of anti-copper therapy (Desai and Kaler, 2008;EASL, 2012). Although direct measurement of free copper is possible, it is not currently routinely available, and most measurements of free copper are not standardized (Twomey et al, 2005(Twomey et al, , 2007El Balkhi et al, 2011). Twenty-four-hour urinary copper excretion is a very important parameter for the diagnosis of WD as well as for treatment monitoring, as it reflects the fraction of free copper in serum (EASL, 2012).…”
Section: Measurement Of Urinary Copper Excretion After 48-h D-penicilmentioning
confidence: 99%